(untitled) (Bangladesh Journal of Medical Science, 2026)
Objective This study compared the effects of regular foot care, foot intrinsic muscle exercises, and ankle mobility exercises on dynamic forefoot pressure (DFFP) and hindfoot pressure (DHFP), strength, and ankle dorsi flexion range of motion in diabetic peripheral neuropathy patients (DPN). Materials and methods Two hundred individuals who were clinically diagnosed with DPN who complied with the inclusion and exclusion criteria were enrolled for this study. The participants were allocated into two groups (100 in each). Group I received standard foot care as per International Working Group on Diabetic Foot guidelines, while Group II underwent foot intrinsic muscle strengthening and ankle mobility exercises, along with usual foot care over eight weeks. The primary outcome measures dynamic forefoot & hind foot pressures were measured by insole pressure sensors, and the secondary outcome measures Foot intrinsic muscle strength (FIMS) and Ankle dorsiflexion range of motion (ADROM) were measured by the Enhanced paper grip test and Universal goniometer, respectively. The measurement was taken before and after 8 weeks of treatment. These scores were recorded and analysed using paired and unpaired t-tests. Results The intragroup difference observed in both groups was statistically significant (p<0.001).The mean value analysis reveals that, regarding between-group analysis of all the dependent variables, regular foot care along with foot intrinsic muscle strengthening exercise and ankle mobility exercise was more effective than regular foot care alone in positively improving DFFP and DHFP, the power of foot intrinsic muscle and ankle dorsiflexion movement among DPN patients (p<0.001). Conclusion In DPN patients, the management of DFFP and DHFP, FIMS, and ADROM is more effective when regular foot care is combined with foot intrinsic muscle strengthening exercise and ankle mobility exercise than when regular foot care is performed alone. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S236-S243